Ответы и объяснения

2012-01-22T13:31:25+00:00

3(x-7)-6x=-x                 5(x+4)+x=6                    7-(2x+3)=9

3(x-7)-6x+x=0               5(x+4)+x-6=0                 7-(2x+3)-9=0

3(x-7)-5x=0                   (5x+20)+x-6=0              -2-2x-3=0

3x-21-5x=0                    5x+20+x-6=0                -5-2x=0

-2x-21=0                        6x+14=0                        -2x-5=0

-2x=21                           6x=-14                            -(2x+5)=0

2x=-21                           x=(-14):6                       ( 2x+5)(-1)=0

x=(-21):2                        x=-⁷₃                              2x+5=0

x=-10,5                                                                2x=-5

                                                                            x=(-5):2

                                                                            x=-2,5